The Resolution of Conflict : Constructive and Destructive Processes - Deutsch, Morton (Carl Hovland Memorial Lectures Series, 2022)
Conflict is a natural and inevitable part of our personal and social lives. In this volume Morton Deutsch, the distinguished social psychologist, explores the factors that determine whether the outcome of conflict will be fruitful or destructive. He examines conflict at the intrapsychic, interpersonal, and intergroup levels and formulates meaningful cross-level generalizations about the determination of conflict resolution.